Language Shift of the Javanese in Stabat - Juliansyah Juliansyah; Amrin Saragih; Busmin Gurning (LINGUISTIK TERAPAN, 2015)
This research addresses language shift of the Javanese in Stabat. It is aimed at finding out the factors influence language shift of Javanese, the pattern of the language shift, and the reasons of Javanese shift into Bahasa Indonesia. The data were obtained from the Javanese families living in Stabat. The study employs qualitative research design with a single case study to get the understanding on this study. The subjects of the study were 10 Javanese families in Stabat. The subjects were divided into two groups, namely parents and children. The reason for dividing the subjects into two groups is because language shift happens across the generation. Questionnaires and interview were used to gain the data. The data were analyzed by using data collection, data reduction, data display and data verification. The findings show that there are eight factors which influence Javanese shift into Bahasa Indonesia in Stabat, namely bilingualism, migration, economic, social, demographic and institutional factors, attitude, and lack of speaking competence. The dominant factor which affects the shift is the institutional factor. The analysis data indicates that the shift occurs in two patterns; in the pattern of relationship between parents and children, and the relationship among children. The status of Bahasa Indonesia as the official language and social success are the reasons for Javanese to shift into Indonesian language. Key words: shift, Javanese, bilingualism, attitude.